Volatile molecular markers of VOO Thermo-oxidation: Effect of heating processes, macronutrients composition, and olive ripeness on the new emitted aldehydic compounds. (April 2018) - Oueslati, Imen; Manaï, Hédia; Madrigal-Martínez, Mónica; Martínez-Cañas, Manuel A.; Sánchez-Casas, Jacinto; Zarrouk, Mokhtar; Flamini, Guido
Abstract: Heating operation has been applied to Chétoui extra-virgin olive oils (EVOOs) extracted from fruits with several ripening stages (RS). The studied samples, were subjected to microwave and conventional heating. Results showed that heated VOOs after 2.5 h and 7 min of conventional and microwave heating, respectively, gave rise to a drastically decrease of LOX products and allowed the detection of toxic new formed aldehydic volatiles (alkanal: nonanal, alkenals: ( Z )-2-heptenal and ( E )-2-decenal, and alkadienals: ( E . E )-2.4-decadienal), which can be used as markers of VOO degradation. Their abundance in the VOO headspaces depends on their boiling points, the rate of their possible degradation to yield other compounds, on the heating processes and on the rate of macronutrients. The emission rate of the new synthesized volatiles during heating processes was mainly attributed to enzymatic oxidation of some fatty acids. Hexanal, ( Z )-2-heptenal, ( E )-2-octenal, ( E )-2-nonenal, ( E, E ) and ( E, Z )-2, 4-decadienal, and ( E, E )-2, 4-nonadienal, derived from linoleic acid, and heptanol, octanal, nonanal, decanal, ( E ) and ( Z )-2-decenal, ( E )-2-undecenal, and ( E, E )-2, 4-nonadienal, are emitted after degradation of oleic acid. During thermo-oxidation, the ECN44 (LLO, and OLnO), and the ECN46 (OLO, and PLO + SLL) compounds decreased, whereas, the ECN48 (OOO, and PPO), and the ECN50 (SOO) compounds increased when temperature and heating time increased. The several variations of the studied biochemical compounds depend to the heating processes. Ripening stage of olive fruits can be used as a tool to monitor the emission rate of the aldehydic volatiles, but cannot be used for a chemometric discrimination. Graphical abstract: Unlabelled Image Highlights: Behavior of VOO volatiles was carried out during microwave and conventional heating. Toxic volatile aldehydes were the abundant new emitted compounds during heating. The new emitted aldehydes are the molecular markers of VOO Thermo-oxidation. Ripening stage is a tool to monitor the emission rate of the aldehydic volatiles. The abundance new emitted volatiles depend to the VOO macronutrients.